Development of Biodegradable Straw using Combination of Unused Rice and Rice Bran - Herliana Valentia Putri; Mohammad Affan Fajar Fallah (APTA and DTIP FTP UGM, 2021)
Plastics waste has been recently recognized as one of the most critical environmental issues. The most plastic is not recycleable and it takes 300-500 years to degraded perfectly. Plastics straw also contribute these negative impacts, so develop the biodegradable straw can be one of the solution. Natural ingredients that contain carbohydrates can be used as biodegradable straw materials are unused rice and rice bran, with glycerin from used cooking oil. This study aims to find out the effects of composition of unused rice flour and rice bran flour respectively on parameters. The parameters are the tensile strength, elongation, water uptake, and the biodegradation, then compare to the control. Statistical test were used to check, analysis, and compare between the data. The results show that combination variations in raw material flour had a significantly effect (p<0.05) on tensile strength, elongation, and biodegradation, but had not significantly effect (p≥0.05) on water uptake. Results obtained from the study of biodegradable straws for tensile strength ranges from 0.21-6.19 MPa, elongation range from 0.43-1.71%, water uptake 100%, and degraded 100%. Sample with a combination of 3 g unused rice flour : 0.5 g rice bran flour, has the highest tensile strength and elongation value and degraded within 4 days. However, the sample can not be used as an alternative to plastic straw because it does not have similar characteristics.